2019
DOI: 10.1093/jac/dkz048
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin and rifabutin resistance in 1003 Mycobacterium tuberculosis clinical isolates

Abstract: Drug-resistant TB remains a public health challenge. Rifamycins are among the most potent anti-TB drugs. They are known to target the RpoB subunit of RNA polymerase; however, our understanding of how rifamycin resistance is genetically encoded remains incomplete. Here we investigated rpoB genetic diversity and cross-resistance between the two rifamycin drugs rifampicin and rifabutin. Methods: We performed WGS of 1003 Mycobacterium tuberculosis clinical isolates and determined MICs of both rifamycin agents on 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
(41 reference statements)
3
32
0
2
Order By: Relevance
“…However, in the case of RFB, a greater proportion of isolates harboring rpoB mutations had MIC values lower than the CC (0.5 μg/ml as recommended by the kit instructions). Possibly, mutations (especially rpoB Asp435Val) assumed to confer resistance to RIF might not be highly correlated with RFB resistance, as found previously by others [26,28,29]. Furthermore, we found that isolates carrying rpoB Asp435Val alone had significantly lower MIC values for RFB than did isolates carrying rpoB Ser450Leu.…”
Section: Plos Onesupporting
confidence: 62%
“…However, in the case of RFB, a greater proportion of isolates harboring rpoB mutations had MIC values lower than the CC (0.5 μg/ml as recommended by the kit instructions). Possibly, mutations (especially rpoB Asp435Val) assumed to confer resistance to RIF might not be highly correlated with RFB resistance, as found previously by others [26,28,29]. Furthermore, we found that isolates carrying rpoB Asp435Val alone had significantly lower MIC values for RFB than did isolates carrying rpoB Ser450Leu.…”
Section: Plos Onesupporting
confidence: 62%
“…We expect these tools to facilitate the use of the expanded Mtb classification by scholars of Mtb evolution and public health practitioners alike for applications such as the rapid assessment of potential outbreaks and isolate triage for detailed phylogenetic analyses. Further, low level susceptibility to specific Mtb drugs has been reported for some lineages 21,22 . Improving the resolution of classification at the sub-lineage level can allow for a better understanding of these findings and potentially a more refined prediction of drug resistance profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal frameshifting errors occur rarely, but when they do the consequences for protein function are generally catastrophic, and frameshift mutations are generally only observed in nonessential genes. In this context we were intrigued by reports of clinical isolates of Mtb carrying frameshift mutations (11)(12)(13)(14), or nonsense mutations (12,(29)(30)(31), in the essential gene rpoB. Surprisingly, none of the publications reported any experimental analysis of the mutations or explained how these mutants were viable.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the functional importance of reading frame maintenance during translation it is surprising that there have been published reports of frameshift mutations in the essential gene rpoB among rifampicin-resistant clinical isolates of Mycobacterium tuberculosis (Mtb) (11)(12)(13)(14). To our knowledge none of these mutants have been investigated to determine either the validity of the mutation reported or a possible mechanism that could explain bacterial viability.…”
mentioning
confidence: 99%